Critiques and proposals for improving university service-learning research in the physical activity and sport field: A qualitative inquiry through a thinking with theory approach - Francisco-Garcés, Xavier; Salvador-Garcia, Celina; Chiva-Bartoll, Oscar; Santos-Pastor, Mª Luisa (Revista Complutense de Educación, 2024)
Introduction: The current socio-educational context leads universities to implement pedagogical approaches capable of training students to be socially critical and committed to social justice. Within this scenario, University Service-Learning is considered to be able to satisfy these requirements in different disciplines, with special emphasis on the field of Physical Activities and Sports. Method: This research focuses on understanding how the researchers in the field of PAS (n=13) perceive the research that is carried out regarding this field, with the aim of transforming and improving future research and interventions. Information was collected through two focus groups and then, was analysed through the thinking with theory analytical practice (Jackson & Mazzei, 2012). Results: The results obtained are displayed in a non-linear network of categories. Among the benefits derived from research in USL in PAS, understanding the educational phenomenon and proposing guidelines and orientations for future interventions and research arise as two relevant ideas. Regarding the weaknesses, participants report a lack of active participation of social groups in research processes, as well as the need to enhance methodological rigor and how results are disseminated. Discussion: In short, tacking stock on the research processes and analysing them critically is necessary to contribute to and strengthen the field of study.